Analysis of Student’s Chemical Literacy on Buffer Solution Material using the Rasch Model at SMAN 1 Tilatang Kamang - Trisna Desviani; Eka Yusmaita (Edukimia, 2023)
The purpose of this study was analyze the level of chemical literacy of students at SMAN 1 Tilatang Kamang on the buffer solution material using the Rasch model with the Winstep application. This research method is a descriptive study with a quantitative approach with a sample of 75 students of 3th grade students at SMAN Tilatang Kamang. The chemical literacy test was carried out using a chemical literacy-based question instrument amount 11 items. Data on chemical literacy test results were analyzed using the Rasch model. Scalogram analysis based on the ability of student who have high abilities is 35L and student who have lowest ability is subject 02L. Based on the level of difficulty of the items, the most difficult item is number 8 (theme 4) and the easiest item is number 10 (theme 6). Most of the chemical literacy analysis description of students at SMAN 1 Tilatang Kamang are at the Scientific Illiteracy level of 39%.